EVALUATION OF ANTIHYPERGLYCAEMIC EFFECT OF BUTEA MONOSPERMA LEAF EXTRACT ON ADRENALIN INDUCED AND HIGH GLUCOSE FEED ANIMAL MODEL - Ray, Biswaranjan; Mahapatra, Santosh Kumar; Behera, Pradipta Kumar; Panigrahi, Ashok K (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: As per the ethnopharmacological information has Butea monosperma been used to treat diabetes mellitus by the tribal people of tropical and subtropical areas. However, there is no much more scientific report available about the antidiabetic property of the leaves of the plant. Hence, the study was undertaken to evaluate the antidiabetic effect of ethanolic extract of B. monosperma on blood levels of adrenaline-induced and glucose feed diabetic rabbits. Methods: The three different doses of the extracts (100, 200, and 400 mg/kg) were administered orally to an experimental animal. The animals were induced diabetics by adrenaline and high glucose diet. Blood glucose level was measured accordingly. For antidiabetic activity, photocolorimeter was used to monitoring the blood glucose level with crest kit box (GOP-POD method). Results: The extracts showed considerable dose-dependent activity. However, the dose 400 mg/kg showed considerable lower of blood glucose level. p<0.01 indicates the significance result. 8 hrs reading 182.5Â±3.83 for 400 mg does is most effective for reducing blood sugar. Conclusion: The study indicates that the ethanolic extract of B. monosperma leaves possesses antidiabetic properties which suggest the presence of biologically active components.